1979
DOI: 10.1111/j.1476-5381.1979.tb13682.x
|View full text |Cite
|
Sign up to set email alerts
|

Improved Insulin Receptor Assay: Effects of an Antidiabetic Sulphonylurea on Liver Membrane Insulin Receptors From Obese Hyperglycaemic Mice

Abstract: A simple assay of liver membrane insulin receptors is described, under conditions which apparently stabilized the insulin‐receptor complex. The receptor population was measured in the presence of physiological doses of radioactive hormone under conditions which minimized negative co‐operativity effects. Equilibrium between receptor and hormone was attained in vitro within 60 min of incubation time at 13°C with no apparent loss of binding sites after 3 h of incubation. Liver membranes from lean mice possessed 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

1981
1981
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…Chlorpropamide is able to inhibit glucose output from the liver in patients with type 2 diabetes (Best, Judzewitsch, Pfeifer, Beard, Halter and Porte 1982); glipizide reduces in rats glucosamineinduced glycogenolysis (Block, Daturi and Tommasini 1980a), and chlorpropamide reduces glucagon-induced glycogenolysis in the perfused rat liver (Blumenthal and Whitmer 1979). On the other hand, evidence has accumulated that long-term treatment with SUs increases the responsiveness of hepatocytes (Greenstein 1979), muscular cells (Feldman and Lebovitz 1969;Bloch, Daturi and Tommasini 1980b) and adipocytes (Maloff and Lockwood 1981) to insulin. Insulin receptors studies were not performed in our trial; further investigations are required to evaluate if the effect of the two SUs is mediated by modifications of the number of insulin receptors (Feinglos and Lebovitz 1978) or by modifications in their binding affinity for insulin (Maloff and Lockwood 1981).…”
Section: Discussionmentioning
confidence: 96%
“…Chlorpropamide is able to inhibit glucose output from the liver in patients with type 2 diabetes (Best, Judzewitsch, Pfeifer, Beard, Halter and Porte 1982); glipizide reduces in rats glucosamineinduced glycogenolysis (Block, Daturi and Tommasini 1980a), and chlorpropamide reduces glucagon-induced glycogenolysis in the perfused rat liver (Blumenthal and Whitmer 1979). On the other hand, evidence has accumulated that long-term treatment with SUs increases the responsiveness of hepatocytes (Greenstein 1979), muscular cells (Feldman and Lebovitz 1969;Bloch, Daturi and Tommasini 1980b) and adipocytes (Maloff and Lockwood 1981) to insulin. Insulin receptors studies were not performed in our trial; further investigations are required to evaluate if the effect of the two SUs is mediated by modifications of the number of insulin receptors (Feinglos and Lebovitz 1978) or by modifications in their binding affinity for insulin (Maloff and Lockwood 1981).…”
Section: Discussionmentioning
confidence: 96%
“…Direct effects on the pancreas can be demonstrated in vitro by a concentration of glibenclamide as low as 2 nmol/1 [42]. In addition it is known that sulphonylureas are without effect in totally pancreatectomized animals [43], and in insulin-dependent diabetics [44], but it has been shown that sulphonylureas may increase insulin receptors in target tissues [45,46]. From available evidence it seems likely that the main effect of sulphonylureas in non insulin dependent diabetes, is to increase the sensitivity of the B-cell response to changes in blood glucose concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Metformin directly affects insulin receptor binding in a variety of cell systems [4,5,6,11]. It selectively increases the number of low affinity binding sites [4,5].…”
Section: Introductionmentioning
confidence: 99%